Student’s involvement in classroom among Diploma Student’s in University Technology Mara, Kedah / Ahmad Hakimi Abu Bakar...[et al.] - Abu Bakar, Ahmad Hakimi; Hasbullah, Intan Syafinas; Bokhair, Nadia; Hassan, Siti Nor Hidayah; Sajahan, Mohamed Samsudeen (2010)
According to Alexander W. Astin (1999)1, student involvement can be defined as student contribution in academic experience. This means that, there is involvement in classroom when the students give their time, energy and effort in the class. Involvement in class is very important for students. This is because it can help to develop conducive environment where the process of learning will become interesting. Besides, it can increase the level of understanding toward the subject learned. Apart from that, involvement in a classroom can be consider as an essential element in helping the university to develop quality graduate for the job market. This study is conduct in order to improve the level of UiTM Kedah student’s involvement in classroom. It is done to investigate whether UiTM Kedah students participate in classroom or not and what are the best ways to encourage them to actively participate in classroom There are several objectives to be achieved in this study whereby to determine the relationship between interaction and the level of student’s involvement in classroom. Besides, to investigate whether learning styles and teaching method influences student involvement in classroom. The research conducted by using Statistical of Package for Social Science (SPSS) version 15.0 and the data was analyzed with the Person Correlation. The result indicated that there is significant relationship between interaction and student’s involvement in classroom.